Identification of Adulteration in Vinegar for Forensic Consideration (International Journal of Scientific Research and Management (IJSRM), 2017)
In this study 12 suspected vinegar samples were collected from the street market as well as from local sellers and the Beauro of standards (BIS) which is assumed as standard, tested for various adulterant as well as comparative study for total solids, total ash, of acidity for suspected vinegar samples and BIS i.e., the presence of mineral acid by mineral acid test, test for presence of caramel, determination of total solids, determination of total ash, and determination of acidity. After examination of suspected vinegar sample it was concluded that all the samples were adulterated and did not follow the BIS standard.